2004
DOI: 10.1038/modpathol.3800140
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of BCL-3 in lymphoid neoplasms: a survey of 353 cases

Abstract: The bcl-3 gene at chromosome 19q13 encodes a member of the IjB family involved in regulating the NFjB pathway. Originally identified by its involvement in the rare t(14:19)(q32;q13), BCL-3 expression has never been analyzed in a wide variety of lymphomas. We assessed BCL-3 expression in 353 cases of non-Hodgkin lymphoma and Hodgkin lymphoma using formalin-fixed, paraffin-embedded tissue specimens, a monoclonal antibody specific for BCL-3, and immunohistochemical methods. Of 172 B-cell lymphomas, 10 (6%) were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
2
36
0
1
Order By: Relevance
“…[1][2][3]5,11,[13][14][15][16][17][18] In agreement with these findings, immunohistochemical studies have identified the presence of BCL3 expression in both B-and T-cell lymphomas pointing to a role of BCL3 in B-and T-cell lymphomagenesis. 33,34 The major aim of the present study was to perform a thorough cytogenetic, FISH, molecular and histopathologic study of B-cell malignancies bearing a t(14;19)(q32;q13) or variant translocations to shed further light on these pathologic associations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5,11,[13][14][15][16][17][18] In agreement with these findings, immunohistochemical studies have identified the presence of BCL3 expression in both B-and T-cell lymphomas pointing to a role of BCL3 in B-and T-cell lymphomagenesis. 33,34 The major aim of the present study was to perform a thorough cytogenetic, FISH, molecular and histopathologic study of B-cell malignancies bearing a t(14;19)(q32;q13) or variant translocations to shed further light on these pathologic associations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, t(14;19) translocations involving BCL-3 have been identified in some lymphomas (Nakagawa et al, 1995;Yano et al, 1995;McKeithan et al, 1997;Au et al, 2002;Soma et al, 2006) and occasionally in lymphoproliferative disorders (Michaux et al, 1996); furthermore, other genetic alterations on chromosome 19 may also lead to increased BCL-3 expression (Schlette et al, 2005). The hypothesis that increased expression of BCL-3 contributes to human B-cell malignancies is supported by several findings: (1) transgenic mice in which BCL-3 is under the control of the m heavy chain enhancer develop splenomegaly and have excess mature B cells in their bone marrow and lymph nodes (Ong et al, 1998); (2) overexpression of BCL-3 can transform mouse 3T3 cells in culture (Viatour et al, 2004); (3) overexpression of BCL-3 can enhance the survival of activated T cells (Mitchell et al, 2001) and (4) elevated levels of BCL-3 are seen in many lymphoid and non-lymphoid human tumor samples (Cogswell et al, 2000;Rassidakis et al, 2003;Canoz et al, 2004;Pallares et al, 2004;Ohno et al, 2005;Schlette et al, 2005). Oncogenically activating mutations within the coding region of BCL-3 have not been identified; however, such mutations may exist in that certain point mutations can enhance the transforming activity of BCL-3 in vitro (Viatour et al, 2004).…”
Section: Multiple Familial Trichoepitheliomamentioning
confidence: 99%
“…In addition to its relatively high expression in B-CLLs carrying the t(14;19) translocation, Bcl-3 has also been found to be elevated in a number of other human cancers, including nasopharyngeal carcinoma (Thornburg et al 2003), breast cancer (Cogswell et al 2000), lymphoma (Canoz et al 2004), and hepatocellular carcinoma (B. O'Neil, unpubl.). To understand the consequences of Bcl-3 constitutive expression and to investigate its potential role in driving oncogenesis, we engineered the MCF-7 breast cancer cell line to express relatively high levels of Bcl-3 (MCF-7B).…”
Section: Elevated Bcl-3 Expression Inhibits Dna Damage-induced Apoptosismentioning
confidence: 99%
“…In this regard, expression of Bcl-3 is sufficient to transform NIH3T3 cells (Viatour et al 2004). Importantly, Bcl-3 has now been shown to be more widely expressed in cancer, with expression in a significant number of breast cancers (Cogswell et al 2000), nasopharyngeal carcinomas (Thornburg et al 2003), lymphomas (Canoz et al 2004), and hepatocellular carcinomas and pancreatic cancers (B. O'Neil, unpubl.). The findings that Bcl-3, in complex with p52, can promote transcription of the genes encoding the cell cycle regulator cyclin D1 and the anti-apoptotic Bcl-2 protein suggest one potential oncogenic mechanism (Westerheide et al 2001;Viatour et al 2003), but a more complete understanding of the role of Bcl-3 in human cancers is still lacking.…”
mentioning
confidence: 99%